2006
DOI: 10.1007/s10529-005-5931-3
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Antibiotic Resistance Genes in Taq Polymerases and a Decontamination Method Applied to the Detection of Genetically Modified Crops

Abstract: Different antibiotic resistance (AR) genes, such as Bla, Tet and NPTII, contaminate commercially available Taq polymerases. The specificity of the AR gene PCR can be increased when using a restriction enzyme-based decontamination of polymerase. The elimination of Taq polymerase contamination allows the use of PCR tests to screen seeds (corn) and processed food for the presence of genetically modified organisms (GMO) based on the detection of AR genes. Without a decontamination procedure for AR genes, PCR scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…In the studies analyzed, common antibiotic resistance gene sequences had been found from Enterobacter cloacae and Serratia marcesens . These two pathogens are increasingly resistant to multiple or most antimicrobial drug classes and the presence of resistance genes in clinical samples would not be surprising or questioned 14,15,17,45 . Consequently, the choice of antimicrobial treatment would be misguided towards reserve antimicrobials that are more toxic than standard ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies analyzed, common antibiotic resistance gene sequences had been found from Enterobacter cloacae and Serratia marcesens . These two pathogens are increasingly resistant to multiple or most antimicrobial drug classes and the presence of resistance genes in clinical samples would not be surprising or questioned 14,15,17,45 . Consequently, the choice of antimicrobial treatment would be misguided towards reserve antimicrobials that are more toxic than standard ones.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids are naturally occurring circular shaped pieces of extrachromosomal DNA, which can replicate independently from the host DNA and can be transferred into samples via multiple routes 43,44 . Complete expression vector sequences have not been identified in commercially available enzyme preparations although fragments interfered occasionally with sequencing studies 14,15,17,41,42,45 . For example, Tenover et al ., had to use a native Taq polymerase to avoid false-positive test results when evaluating samples for the presence of antibiotic resistance genes such as Bla Tem-1 because most expression vectors used for generation of the enzyme also had this resistance gene 46 .…”
Section: Introductionmentioning
confidence: 99%
“…nptll) have been detected in com mercially available Taq polym erase preparations (prepared by recom binant D NA techniques) used in the PC R am plification process, and may therefore lead to false-positive reporting w hen screening for GM Os based on selectable m arker gene sequences such as n p tll (Perron et al, 2006) (Germini et al, 2005;Leimanis et al, 2006). M icroarray technology utilizes microscopic arrays o f oligonucleotide probes im m obilized on solid supports.…”
Section: List Of Tablesmentioning
confidence: 99%